A resonant ultrasound spectroscopy study of novel materials: nanocrystals, quasicrystals, and hydrogen-storage alloys - Agosta, Dennis Salvatore, author; Leisure, Robert G., advisor; Gelfand, Martin P., committee member; Heyliger, Paul R., committee member; Patton, Carl E., committee member (Colorado State University. Libraries, 2006)
The experimental technique Resonant Ultrasound Spectroscopy (RUS) has been used to study the elastic properties and ultrasonic loss of several novel materials: a nanocrystalline form of palladium, a quasicrystal, a Laves phase C15 cubic material that undergoes a Martensitic phase transition when cooled, and a random alloy. Resonant Ultrasound Spectroscopy (RUS) is an ideal technique for the characterization of the elastic properties of these types of materials since RUS is nondestructive and can work with very small sample sizes. The RUS technique is also sensitive to ultrasonic loss, and these measurements provide information on internal mechanisms that dissipate energy such as the movement of light interstitial atoms or the movement of dislocations. Nanocrystalline materials have average grain sizes of 100 nm or less. The reduced grain size leads to physical properties that are different than the properties of the coarser grained forms of the same chemical composition, and many of these properties are the basis of new technological advances. The elastic constants of nanocrystalline palladium (nc-Pd) and silicon-stabilized nanocrystalline palladium (nc-PdSi) were measured in the temperature range 4-300K. The measured bulk modulus for nc-Pd is 35.1-40.0% lower than corresponding values calculated for polycrystalline Pd. The measured shear modulus is 17.8-18.6% lower than pc-Pd. The elastic moduli for nc-Pd exhibit significant anleastic effects, while the elastic moduli for nc-PdSi do not. A loss peak centered near 264 K in nc-Pd is suppressed in nc-PdSi, indicating the loss mechanisms are due to grain boundary effects. Quasicrystals are materials with an aperiodic structure, but which display perfect long-range order. While periodic crystalline structures can only display 2-fold, 3-fold, 4-fold and 6-fold rotational symmetries, quasicrystals display 5-fold, 8-fold, 10-fold and 12-fold rotational symmetries. RUS was used to measure the elastic constants of an icosahedral Ti39.5Zr39.5Ni21 quasicrystal over the temperature range 3- 292K. The results were in general agreement with earlier ultrasonically-derived values for i-phase Ti41.5Zr41.5Ni17. In comparison to many other i-phase materials, the ultrasonic measurements show that the TiZrNi materials have a low shear modulus to bulk modulus ratio, and a high Poisson's ratio, suggesting that the interatomic bonding in the TiZrNi materials differs substantially from that in many of the other i-phase materials. A Debye temperature of 316.7 K was calculated from the low-temperature elastic constants, and the internal friction increases rather strongly in the temperature range of 150 - 300 K, suggestive of a thermally activated process. Laves-phase alloys are the largest subgroup of the topologically close-packed materials, and are characterized by low densities and high melting points. The Laves-phase C15 (cubic) materials can absorb hydrogen, making them useful in battery and fuel cell technologies. The temperature dependence of the elastic constants of polycrystalline ZrV2 was measured in the temperature range 100-300 K using the RUS technique. The elastic constants exhibit anomalous behavior over this temperature range, and the lack of hysteresis in the temperature dependence of the resonant frequencies provides evidence that the phase transition from the C l5 cubic to rhombohedral form is second-order. Ultrasonic loss was measured for the first resonant frequency and displays a peak centered at the transition temperature, Tm. Calculations of the Debye temperature using room temperature elastic constants agree well with results published by earlier studies. Random alloys are metallic compounds which do not exhibit chemical ordering of their component atoms; any lattice position may be inhabited by any of the chemical species comprising the compound. The random alloy discussed in this study, Ta0.33V0.67, can absorb considerable amounts of hydrogen and the disordered nature of the local atomic environments leads to differences in the elastic properties. In this study, the temperature dependence and ultrasonic loss for a random alloy with the same chemical composition as the Laves-phase C15 TaV2 compound was measured in the temperature range 5-300 K using the RUS technique, and compared to an earlier study of TaV2. The temperature dependence of the bulk modulus of bcc Ta0.33V0.67 exhibits strong agreement with the semi-empirical Varshni expression, while the shear modulus and Young's modulus deviate significantly from this theoretical curve. Laves-phase C15 TaV2 also exhibits an anomalous temperature dependence of G and E, but where TaV2 exhibits a decreasing modulus with decreasing temperature, bcc Ta0.33V0.67 exhibits an increasing modulus with decreasing temperature. The electronic effects which strongly impact the C44 elastic constant in C15 TaV2 are highly suppressed in the random alloy form, resulting in a temperature dependence of the shear and Young's moduli that are only slightly anomalous and which display a more normal behavior. Ultrasonic loss associated with the movements of hydrogen atoms between interstitial tetrahedral sites is observed for bcc Ta0.33V0.67H0.045 in the 170 K temperature region, and is not observed for bcc Ta0.33V0.67.
Keywords: condensation; condensed matter physics